Effects of Filler Modification on the Properties of Elastomeric Composites - Janik, Robert; Labaj, Ivan; Skalkova, Petra; Durisova, Silvia; Moricova, Katarina (Manufacturing Technology Journal, 2024)
The application of cellulose (CEL) as a filler in elastomeric composites (ECs) was studied, with cellulose examined in its untreated form (RAW), after DCSBD plasma modification, and ozone pre-treatment. Changes in surface fluorescence demonstrated that DCSBD plasma-modified cellulose achieved better dispersion in the elastomeric composite mixture, which also showed improved strength and elongation in static tensile tests. DMA analysis confirmed changes in visco-elastic properties, with DCSBD plasma-modified cellulose altering the glass transition temperatures of the Elastic and Loss modulus, as well as Tan Delta. SEM microscopy did not conclusively demonstrate the reinforcing effect of plasma-modified cellulose. Small property changes were observed with ozone pre-treated cellulose, similar to the unmodified cellulose composite mixture (NR).
Keywords: Ozone; DCSBD plasma; Cellulose; Composites; DMA analysis